2020
DOI: 10.1093/mnras/staa883
|View full text |Cite
|
Sign up to set email alerts
|

Massive discs around low-mass stars

Abstract: We use a suite of SPH simulations to investigate the susceptibility of protoplanetary discs to the effects of self-gravity as a function of star-disc properties. We also include passive irradiation from the host star using different models for the stellar luminosities. The critical disc-to-star mass ratio for axisymmetry (for which we produce criteria) increases significantly for low-mass stars. This could have important consequences for increasing the potential mass reservoir in a proto Trappist-1 system, sin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 92 publications
2
22
0
Order By: Relevance
“…Common assumption is that GI requires q 0.5, therefore rendering these discs too low mass to generate prominent self-gravitating structure. However it may be possible for discs to display self-gravitating spirals for much lower mass ratios than previously thought, with the critical mass ratio having a strong dependence on the host star mass and disc opacity (Veronesi et al 2019;Cadman et al 2020;Haworth et al 2020). We therefore should caution against discarding GI as a plausible mechanism based off this simple mass criterion alone.…”
Section: Conclusion On Dsharp Samplementioning
confidence: 87%
“…Common assumption is that GI requires q 0.5, therefore rendering these discs too low mass to generate prominent self-gravitating structure. However it may be possible for discs to display self-gravitating spirals for much lower mass ratios than previously thought, with the critical mass ratio having a strong dependence on the host star mass and disc opacity (Veronesi et al 2019;Cadman et al 2020;Haworth et al 2020). We therefore should caution against discarding GI as a plausible mechanism based off this simple mass criterion alone.…”
Section: Conclusion On Dsharp Samplementioning
confidence: 87%
“…Most notably, Vorobyov (2013) performed simulations of disk gravitational fragmentation and found that they were unable to produce brown dwarf companions at small orbital separations. Furthermore, Kratter et al (2010), Offner et al (2010), andHaworth et al (2020) found that disk fragmentation is less likely around M-dwarf primary stars. We suggest, thus, that some circumstantial evidence exists to support the formation of ET Cha B via core fragmentation in the proto-stellar cloud.…”
Section: The Formation Of the Et Cha Systemmentioning
confidence: 99%
“…If spirals are predominately produced by giant planets, then the detection rate of such spirals can directly inform us about the occurrence rate and properties of giant planets (Hall et al 2017;Forgan et al 2018a;Dong et al 2018a). If, on the other hand, most spirals are caused by GI, their existence and morphology can be used to infer fundamental disc properties, such as disc mass (Dong et al 2015a;Haworth et al 2020;Cadman et al 2020), and therefore constrain planetary mass budgets and formation timescales (Nayakshin et al 2020) on a comprehensive scale.…”
Section: Introductionmentioning
confidence: 99%